RATIO DECIDENDI ATAS KONSTRUKSI DAKWAAN PENUNTUT UMUM DELIK PENGGELAPAN ARISAN ONLINE (PUTUSAN NO 30/PID/2021/PT SMG) - Luthfi Khansa Rasendriya Rahyono; Ismawati Septiningsih (Verstek, 2023)
This research aims to analyze and examine the Judges' Legal Considerations regarding the Construction of the Public Prosecutor's Indictment against the perpetrator of the Online Arisan Embezzlement Crime. Regarding how the Judge's Legal Consideration should be for the Online Arisan Crime in Decision Number 30/Pid/2021/PT SMG. Based on the results of research and discussion, it can be seen that the Judge's consideration or ratio decidendi used to determine the perpetrator to be the defendant in Decision Number 30/Pid/2021/PT SMG, according to the author, is correct, as in the online arisan activity there is a criminal act of embezzlement committed by the Defendant. It can also be seen based on the results of the analysis and discussion according to the author in Decision Number 30/Pid/2021/PT SMG, apart from looking at the legal considerations above, the author looks at the prosecutor's charges, which according to the author fall into the category of lenient charges, the indictment can be explained as the prosecutor's conclusion on the examination of the case made based on the evidentiary process at trial. Judges who are the enforcers of justice become the basis for the prosecutor's charges. When considering several charges in cases that have passed, it is appropriate for the public prosecutor to impose heavier charges on the defendant.Keywords: Online Arisan; Ratio Decidendi; Construction of Public Prosecutor's Indictment